Biochemical monitoring of muscle recovery in elite handball using an individualized approach - Henze, A.-S.; Huth, J.; Mauch, F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To evaluate the classification performance of a new method to individualize reference ranges for biomarkers of muscle recovery in elite handball.